Digital technologies in the classrooms in the last decade (2014–2023): a bibliometric analysis - Alam, Talha Mahboob; Stoica, George Adrian; Sharma, Kshitij; Özgöbek, Özlem (Frontiers in Education, 2025)
IntroductionDigital technologies are widely integrated with teaching and learning, and examining these technological interventions in the classrooms has become an active research area. Existing reviews are often constrained, relying on qualitative methods like meta-analysis, scoping review, or systematic review, which tend to cover a limited number of studies. We conducted a bibliometric analysis of 1,128 articles published between 2014 and 2023 from the Web of Science database to provide a comprehensive overview of this field.MethodsThis study used Biblioshiny and VOSviewer tools to perform performance analysis and scientific mapping. In this study, performance analysis was performed, including descriptive statistics, publication trends, and identification of key actors. Furthermore, scientific mapping has also been done to visualize the prevalent structural aspects and hot research topics to observe the evolving dynamics over the past 10 years.ResultsThe findings indicate a significant rise in publications over the past decade, with an annual growth of 21.5 per cent. We identified prolific authors, institutions, journals, countries, articles, and keywords that encapsulate the domain of digital technologies in the classrooms. The prospective challenges were also identified, including a need for a more technology-driven culture, limited teacher assistance, user interface design issues, proper training, and a technological divide.DiscussionThe findings could encourage the use of digital technologies in the classrooms and offer insights for policymakers to (re)allocate resources. Furthermore, this work is valuable for informing scholars and practitioners about the current state of research, helping them to identify and focus on trending topics when deciding which areas to explore.